Educational and Cultural Role of Arab Virtual Document Exhibitions - Elsawy, Elsayed Salah; Attia, Sarah Nagah (Journal of Ecohumanism, 2024)
Archival institutions are legally authorized to preserve educational, historical, or archival documents. Under this context, this research explores the role and interest of Arab archival institutions in displaying official documents on their websites. This study delves into focusing on the service provision of archival institutions by providing a virtual exhibition of their documents. Method of content analysis helps this research analyze the exhibition’s characteristics, for instance, display of document type, size, metadata availability, research tools and instruments, and engraving the possibility to copy, download, or print documents. The sample size of the research included ten archival institutions in Arab, including Oman, Jordan, UAE, Tunisia, KSA, Iraq, Qatar, Libya, and Morocco. These institutes were selected based on the presence of archival document websites that provide text documents, photographs, and visual recordings. The analysis of the research uncovered the aspect that Arab archival institutes differ in their interest in exhibiting virtual documents and the type/number of documents available to the public. However, almost 50% of archival institutes provide metadata for displayed documents. They provide advanced characteristics, such as enlargement of images, search, download, and sharing, available in 33.3% of virtual exhibitions. This study recommends the establishment of control to select displayed documents compatible with different users. Moreover, the display of images and documents should include descriptive data that explains the nature and context of document creation and preservation. Virtual exhibition visitors must be surveyed with. their aspirations under consideration of the archival institute's policies and country-specific document management laws.Educational Service